Nanomaterials’ Application in Architectural Façades in Italy - Ghida, Djamil Ben (Applied Science and Engineering Progress, 2023)
Nanotechnology and nanomaterials are revolutionizing the construction industry by improving material’s durability, strength, and performance. Nanomaterials have a direct impact on building’s energy efficiency, façade aesthetics, urban attractiveness, urban pollution, and built heritage preservation. In this paper, it will be confirmed that nanomaterials are providing cutting-edge technical solutions for the European building stock by addressing current biodeterioration and weathering of buildings, reducing CO2 emissions, and having a positive impact on the building sector as a whole, including structure, surface coatings, energy consumption, and COVID-19 outbreak. The methodology used is exploratory and descriptive, with two Italian case studies analysis thrown in for good mixed-methods analysis. The empirical analysis investigates the environmental health and economic benefits of deploying nanotechnology systems in Italian building facades. The objective of the research is to analyze the characteristics and functions of nanoparticles; demonstrating how nano-features can lower energy use, improve contextual urban quality, preserve architectural historical identity, mitigate coronavirus outbreaks, and eventually change the future design thinking process of architects. The paper’s originality stems from its synoptic approach and holistic analysis of nanomaterials utilized in Italian façade structures.